Four acts of the Council of the Province of New York, passed in July 1729 ({publisher not identified], 1729)
The first two acts concerned the regulating and creating of public high roads in the cities and counties of Albany and Suffolk. The third act set the allowances of the representatives of the County of Suffolk. The final act extended an act set to expire, regarding justices of the peace in the county of Albany.